EDUCATIVE TRADITION AND ISLAMIC SCHOOL IN INDONESIA - Tan, Charlene (SCAD Independent, 2015)
An Islamic school that subscribes to an educative tradition is essentially one that sees compatibility between the inculcation of religious values and the acquisition of ?modern? knowledge and dispositions. This article argues that most Islamic schools in Indonesia reside in an educative tradition as evident in three main ways. First, most Islamic schools in Indonesia are keen to obtain knowledge from both religious subjects and modern ?secular? subjects. Secondly, an increasing number of Islamic schools have incorporated student-centered pedagogies so that their students do not simply learn by rote or memorizations. Thirdly, many Islamic schools provide a variety of student activities to develop the students? life skills and leadership abilities so as to encourage their students to internalize and put into practice the principles and values they have learnt. Notwithstanding its promotion of an educative tradition, many Islamic schools in Indonesia face a perennial challenge in infusing Islamic principles and values into the teaching of modern ?secular? subjects.